The prevalence and factors associated with ever perpetrating intimate partner violence by men receiving substance use treatment in Brazil and England: A cross‐cultural comparison. (5th October 2016) - Gilchrist, Gail; Radcliffe, Polly; Noto, Ana Regina; d'Oliveira, Ana Flávia Pires Lucas
Abstract: Introduction and Aims: Intimate partner violence (IPV) perpetration is common among men who use substances. Substance use is a contributing factor for IPV perpetration. This cross‐sectional study determined lifetime prevalence and factors associated with ever perpetrating IPV by men receiving substance use treatment in Brazil (n = 281) and England (n = 223). Design and Methods: IPV, adverse childhood experiences, attitudes towards gender relations and roles, current health state, substance use, depressive symptoms and anger expression were assessed. Logistic regression determined factors associated with ever perpetrating any (emotional, physical and/or sexual) IPV. Multinomial logistic regression determined factors associated with ever perpetrating different types of IPV. Results: 74.6% (373/500) reported ever perpetrating IPV: 16.5% (82/498) emotional IPV only, 46.4% (231/498) physical IPV (with/without emotional IPV) and 11.6% (58/498) sexual IPV (with/without emotional and/or physical IPV). Higher anger expression, higher depressive symptoms, fighting physically with another man in the past year (Brazil only), experiencing a greater number of adverse childhood experiences and a higher hazardous drinking score (England only) predicted ever perpetrating IPV. Compared to never perpetrating any IPV, anger expression was associated with emotional and physical IPV perpetration; fighting physically with another man in the past year was associated with physical IPV perpetration and experiencing a greater number of adverse childhood experiences and a higher hazardous drinking score were associated with both physical and sexual IPV perpetration. Discussion and Conclusions: Integrated interventions that address IPV and substance use delivered in substance use treatment could improve outcomes for perpetrators and victims.[Gilchrist G, Radcliffe P, Noto AR, d'Oliveira AFPL. The prevalence and factors associated with ever perpetrating intimate partner violence by men receiving substance use treatment in Brazil and England: A cross‐cultural comparison. Drug Alcohol Rev 2017;36:34–51]